An Empirical Investigation of the Associations of Short and Long Debt Policies with’ Economic Values of Energy Sector - Bagais, Omer; Aljaaidi, Khaled; Alothman, Abdulaziz (International Journal of Energy Economics and Policy, 2020)
The purpose of this paper is to empirically investigate the impact of short and long-term debt policies on economic values of energy sector in Saudi Arabia. Pooled OLS Regression model is utilized to analyze eight years of energy companies’ data (2012-2019) to report the association between two measures of capital structure, namely; short-term and long-term debt policies, and firm economic value after controlling for firm size and inventory management. Empirical findings suggest that the two measures of capital structure impact negatively on firm economic value in energy industry in Saudi Arabia. The results of this study have several policy implications for financial managers, banks, investors, auditors, and stock market authority to understand why capital structure impacts the firm sustainability in a negative way. Keywords: Capital structure, firm sustainability, energy industry, Saudi Arabia. JEL Classifications: L25, H63, 86, G51 DOI: https://doi.org/10.32479/ijeep.10498